Pengaruh Komitmen Perusahaan Dan Loyalitas Kerja Karyawan Kontrak Terhadap Kinerja Karyawan Kontrak Pada Restoran Burger King Area Jakarta Pusat - Muhamad Riyan Salam; Agus Sulaiman Anhary (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of organizational commitment and work loyalty on the performance of contract employees at Burger King Restaurant, Central Jakarta Area. The research employed a quantitative method with a survey approach. The population consisted of 150 employees, while the sample comprised 110 respondents determined using the Slovin formula with a 5% error rate and purposive sampling technique, specifically contract employees who have worked for more than three years. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination with the assistance of SPSS software. The results show that partially, organizational commitment has a positive and significant effect on contract employee performance with a t-value of 5.443 and a significance level of 0.000 < 0.05. Work loyalty also has a positive and significant effect on contract employee performance with a t-value of 8.177 and a significance level of 0.000 < 0.05, and it is the most dominant variable in improving employee performance. Simultaneously, organizational commitment and work loyalty significantly influence contract employee performance with an F-value of 82.302 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 0.360 indicates that organizational commitment and work loyalty explain 36.0% of employee performance, while the remaining 64.0% is influenced by other factors outside this study. It can be concluded that improving organizational commitment and work loyalty among contract employees is an important factor in enhancing contract employee performance at Burger King Restaurant, Central Jakarta Area.